Principles and trends on biological control of nematodes with nematophafous fungi - Carneiro, Regina M. D. Gomes (Pesquisa Agropecuaria Brasileira, 1992)
In the last few years the demonstration of nematodes suppression by biological agents and the restrictions to use some nematicides have revived interest in biological control. Most work has been done with the nematode-trapping fungi, and few experiments have been done with endoparasites that attack vermiform nematodes. Fungi that parasitize nematodes eggs are being increasingly studied, and some show promise as biological control agents. Biological control demands a multidisciplinary approach and success depends on detailed knowledge of the agent, host and soil interactions. Detailed studies on biological control of nematodes are few, some general principles have emerged but more research is needed of environmental factors influencing parasitism, production, formulation and incorporation in soil, problems will rarely be solved rapidly. Given financial support to establish research programs, biological control can play an important part in the future management of many of our major nematode pests.